Validation of Two Revised, Simplified Criteria for Assessing Sepsis-Associated Disseminated Intravascular Coagulation in ICU Patients with Sepsis-3: A Retrospective Study - Wang, Bin; Zhang, Bo; Shen, Ying; Li, Jiaoyuan; Yuan, Xu; Tang, Ning (Laboratory medicine, 2023)
Abstract Objective This study aimed to validate the performance of modified Japanese Association for Acute Medicine (m-JAAM) and simplified Japanese Society on Thrombosis and Hemostasis (s-JSTH) criteria in diagnosing coagulation disorders in sepsis and examine their prognostic value compared with sepsis-induced coagulopathy (SIC) and International Society on Thrombosis and Hemostasis (ISTH) criteria. Methods This retrospective study included subjects diagnosed with sepsis (August 2020 to February 2021, n = 296). The m-JAAM, s-JSTH, SIC, and ISTH criteria were evaluated and compared using receiver operating characteristic (ROC) curves and areas under the curve (AUCs). Results There was no significant difference in AUC for predicting in-hospital 28-day mortality by m-JAAM, s-JSTH, SCI, and ISTH criteria (0.745, 0.763, 0.760, and 0.730, respectively). The proportion of patients fulfilling the m-JAAM and SIC criteria was higher than that of the s-JSTH and ISTH criteria (43.2%, 56.1% vs. 25.0%, 22.6%, P < .05). Conclusion The m-JAAM criteria might be more suitable for early-stage disseminated intravascular coagulation of sepsis than s-JSTH criteria.